Teoria pulsu w starożytności - Krajewska, Judyta (Vox Patrum, 2021)
The rhythmic movement of the vessels, involving stretching and contraction of their walls, as a result of the mechanical action of the blood pumped by the heart, provides a lot of important information about the work of our heart, our well-being and emotions. Already in antiquity, its importance for the assessment of measurable life parameters was appreciated. However, not all the names of ancient physicians dealing with this subject are known and included in the narrative of the history of medicine. Praxagoras, Herophilus, and Eratistratos are the names of great physicians who contributed significantly to the study of the pulse, and whose works became the basis for further research on the pulse by Galen of his successors. Marcellinus, a physician that was actually "invisible" in the history of medicine until recently, strongly emphasized in his treatise the need to combine theory and practice in educating future doctors. In his opinion, practical science allowed to refine the ability to correctly assess and measure the heart rate, which was best felt on the wrist. It is ancient medicine that made pulse measurement the basic tool for diagnosing and determining the patient's health problems.